Potensi dan Tantangan Konseling Spiritual untuk Mencegah Ide Bunuh Diri di Kalangan Mahasiswa Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) - Baharuddin, Lutfiah Nabilah; Rohayati, Rizky; Mayasari, Ros (Jurusan Bimbingan dan Konseling Islam, 2025)
The increasing rate of suicide among Indonesian university students reflects a serious mental health vulnerability caused by academic pressure, loneliness, loss of life meaning, and weak social support. This study explores the effectiveness of spiritual counseling in preventing student suicide and revitalizing its application in State Islamic Higher Education Institutions (PTKIN). Using a literature review of studies published between 2015 and 2025 from Google Scholar and Garuda Dikti, the analysis applies a narrative synthesis to identify core themes of concepts, strategies, and implementation models. Results indicate that spiritual counseling reduces suicidal ideation by strengthening life purpose, promoting positive religious coping, easing psychological distress, and stabilizing emotional well-being. Prior studies highlight the efficacy of dzikir therapy, religious reflection, and worship integration in enhancing students’ resilience. The study recommends improving counselor competence, engaging academic advisors, and ensuring institutional support so spiritual counseling becomes an effective preventive and curative mental health strategy.